2018
DOI: 10.1103/physrevd.98.114501
|View full text |Cite
|
Sign up to set email alerts
|

Topological susceptibility of the 2D O(3) model under gradient flow

Abstract: The 2d O(3) model is widely used as a toy model for ferromagnetism and for Quantum Chromodynamics. With the latter it shares -among other basic aspects -the property that the continuum functional integral splits into topological sectors. Topology can also be defined in its lattice regularised version, but semi-classical arguments suggest that the topological susceptibility χ t does not scale towards a finite continuum limit. Previous numerical studies confirmed that the quantity χ t ξ 2 diverges at large corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 52 publications
(100 reference statements)
5
24
0
Order By: Relevance
“…[14] employed a (truncated) classically perfect lattice action, which has very small lattice artifacts, and found that dislocations are not present, while the logarithmic divergence persists. Recently this property was confirmed by applying the gradient flow to the standard action [15]. Remarkably, the same feature was also observed by simulating the topological action [4], for which the semiclassical argument would have suggested a strong power-law divergence.…”
Section: Fractal Cluster Dimension and The Role Of Merons In The 2-d supporting
confidence: 58%
“…[14] employed a (truncated) classically perfect lattice action, which has very small lattice artifacts, and found that dislocations are not present, while the logarithmic divergence persists. Recently this property was confirmed by applying the gradient flow to the standard action [15]. Remarkably, the same feature was also observed by simulating the topological action [4], for which the semiclassical argument would have suggested a strong power-law divergence.…”
Section: Fractal Cluster Dimension and The Role Of Merons In The 2-d supporting
confidence: 58%
“…3 In contrast, at this point we conclude that the topology of the 2d O(3) model seems to be ill-defined in the continuum limit, even after the application of the Gradient Flow. However, this study is going to be extended to even larger L and ξ, in order to further check this conclusion [15] Table A1. A summary of our numerical results in the nine volumes V = L × L that we investigated.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, at t = 0 a power-law cannot be ruled out by the present data, although a logarithmic divergence is expected. We hope for the extension of this study to even larger volumes [15] to be helpful also in this regard.…”
Section: Continuum Limitmentioning
confidence: 92%
See 1 more Smart Citation
“…The most remarkable difference of the CP 1 model from other (N > 2) CP N−1 models is that the semi-classical calculation of the former leads to a UV divergence in the topological susceptibility. This is supported by lattice numerical calculations, unless a suitable counter term is added [50,[57][58][59][60][61][62][63][64]. 7…”
Section: Comparison With the Cp N−1 Modelmentioning
confidence: 90%